#TITLE_ALTERNATIVE# - PRAYOGA (NIM 13202115), YUDHISTIRA
The world of network and internet lean to be insecure and unreliable, therefore, we need a security mechanism that protect data within its delivery process and storage. This mechanism will not allow unauthorized person to access data. Mechanism named here is cryptography and the media that support this mechanism is smart card. Smart card gives authentication service between smart card user and smart card vendor where any information within a smart card is a combination from two huge integer values that special-mathematically connected. To know how strong a Smart Card could have, we need to analyze any cryptographic algorithm embedded within it. The algorithm that we used in this test is ElGamal cryptographic schemes. This final report described the mechanism to generate key pairs on Smart Card using ElGamal cryptography system; its implementation, and also its security and performance. To do this, we implement simple software that shows how this algorithm works and we use 512 bit, 1024 bit and 2048 bit key length parameter as an input. Then we conclude from these researches: for security parameter, ElGamal is more secure than RSA , it will be shown that ElGamal 512 bits has a better security than RSA 1024 bits, and for efficiency parameter ElGamal has the ideal key size that match the size of smart card memory. And finally we can conclude ElGamal cryptography is suitable to use in Smart Card, and perhaps it will be able to replace RSA algorithm in the future.